Dampak Pembelajaran Hybrid Learning Pada Kemampuan Matematis Siswa SMP Kalam Kudus Medan - Ratio Julianci Simarmata (Edumaspul: Jurnal Pendidikan, 2022)
This study aims to determine the impact or influence of the hybrid learning model on student’s mathematical ability. The population of the study was all of the ninth grade students of SMP Kristen Kalam Kudus Medan, with cluster random sampling and the type of the study used quasi-experimental research. The test instrumental of the study was a description test that has been already tested for validity and student observation sheets. From the calculation of the regression analysis, it was obtained with the regression equation for students’ mathematical abilities, namely Y = - 4.901 + 0.872X, from the regression equation, the value of b was positive, the coefficient b was the regression direction coefficient which stated the change in the average variable Y, it meant that two variables had a positive linear relationship and each increase in the variable X by one unit would be followed by an increase in the variable Y with 0.872 unit. From the calculation of the coefficient of determination, the value of r2 was 13.2%, which meant the impact or influence of the hybrid learning was 13.2% on students’ mathematical abilities (Y) while the other was explained by unexamined variables. Keywords: Hybrid learning;mathematical ability